2019
DOI: 10.2196/10902
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Clinician-Orchestrated Virtual Reality Platform for Distraction During Pediatric Intravenous Procedures in Children With Hemophilia: Randomized Controlled Trial

Abstract: BackgroundNeedles are frequently required for routine medical procedures. Children with severe hemophilia require intensive intravenous (IV) therapy to treat and prevent life-threatening bleeding and undergo hundreds of IV procedures. Fear of needle-related procedures may lead to avoidance of future health care and poor clinical outcomes. Virtual reality (VR) is a promising distraction technique during procedures, but barriers to commercially available VR platforms for pediatric health care purposes have preve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
2
29
0
1
Order By: Relevance
“…Many innovative teaching methods such as videos and animations, help nursing students and has the potential to make cancer drug administration less hazardous. Some of them train the students to avoid high-risk situations and provide them with the opportunity to repeat chemotherapy injection techniques via simulations (Dunn et al, 2019;Khan et al, 2017;Rahimi et al, 2019). For safety and ethical considerations, nurse students usually are not allowed to handle toxic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many innovative teaching methods such as videos and animations, help nursing students and has the potential to make cancer drug administration less hazardous. Some of them train the students to avoid high-risk situations and provide them with the opportunity to repeat chemotherapy injection techniques via simulations (Dunn et al, 2019;Khan et al, 2017;Rahimi et al, 2019). For safety and ethical considerations, nurse students usually are not allowed to handle toxic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual reality (VR) has been explored as a novel approach for numerous health applications wherein, threedimensional virtual environments can be explored in real time. VR learning situations can not only minimise the medical negligence caused by clinical technology sparseness but also address the shortcomings of many traditional teachings (Dunn et al, 2019;Schneider & Hood, 2007). However, the question is, will the students gain better knowledge and working attitude after learning?…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one study was excluded as the primary outcomes did not fit the review assumptions. The measured outcomes were safety concerns, effectiveness, usability and engagement of VR during intravenous procedures [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…It reduces pain and anxiety during medical procedures in children, thereby ensuring better adaptation and treatment adherence (Mahrer, 2018). To date, only a handful of randomized controlled trials (RCTs) have investigated the effect of VR on venipuncture/phlebotomy pain management and reported that it helps reduce pain and/or anxiety during venipuncture/phlebotomy procedures (Aminabadi, Erfanparast, Sohrabi, Oskouei, & Naghili, 2012;Chan et al, 2019;Dunn et al, 2019;Gerçeker et al, 2020;Gerçeker, Binay, Bilsin, Kahraman, & Yılmaz, 2018;Mahrer, 2018). According to a systematic review and metaanalysis of the effect of VR on pain and anxiety, although some studies address the effectiveness of VR on pain, there are very few studies examining its effect on anxiety, hence, calling for further research (Eijlers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%